IMPLEMTASI RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA MEDIK AKIBAT KESALAHAN DIAGNOSIS BERBASIS ARTIFICIAL INTELLIGENCE DALAM PELAYANAN KESEHATAN DI INDONESIA - Beni Satria (Berajah Journal, 2026)
The rapid adoption of Artificial Intelligence (AI) in diagnostic processes across Indonesian healthcare facilities has not been matched by an adequate legal framework for determining liability when an AI system produces a diagnostic error that harms a patient. The retributive approach embodied in the criminal sanctions of Article 440 and Article 447 of Law Number 17 of 2023 on Health is considered insufficiently capable of addressing the complex relationship between medical personnel, healthcare providers, and technology developers in AI-based medical crimes. This study aims to analyze the characteristics of medical crimes arising from AI-based diagnostic errors and to examine the relevance of restorative justice as an alternative dispute resolution mechanism in Indonesian healthcare services. The study employs a normative juridical method using statutory and conceptual approaches, analyzed descriptively and qualitatively on primary, secondary, and tertiary legal materials. The findings show that the absence of specific technical regulation on medical AI generates uncertainty in determining the subject of criminal liability, while the restorative justice principles under Attorney General Regulation Number 15 of 2020 could potentially be adapted for such cases, provided that intent (mens rea) is not dominant and patient harm can be restored through relationship-based recovery mechanisms. The study recommends the formulation of technical guidelines for applying restorative justice specifically to AI-based medical crimes, coupled with strengthened algorithm auditing and safety certification of medical AI systems.